Pemodelan Kondisi Optimum Ekstraksi dan Identifikasi Senyawa Penyusun Minyak Atsiri Lada Hitam - Shintawati, Shintawati; Analianasari, Analianasari; Zukryandry, Zukryandry (Politeknik Negeri Lampung, 2021)
Black pepper is a spice with a spicy taste and a distinctive aroma that has become known as the King of Spices. The distinctive aroma of black pepper comes from the volatile compounds that make up the essential oil of pepper. Black pepper essential oil has antimicrobial properties that can relieve respiratory infections and relieve muscle disorders. The acquisition of pepper essential oil from the distillation process is influenced by operating conditions. The aim of this study was to identify the composition of black pepper essential oil compounds using GCMS and to optimize the operating conditions (material size, solvent ratio, and distillation time). The method used to determine the optimum condition is using the Response Surface Method (RSM). The results showed that the highest yield of black pepper essential oil from this experiment is 5.14%. The empirical model was also suitable for the experiment and the optimum conditions for producing the maximum pepper oil yield 5,81% were 40 mesh of material size, 0.12 (g.ml-1) of solvent ratio and 162 minutes of distillation time. GCMS test results showed that the main constituents of pepper essential oil are caryophyllene, ocimene, limonene, carene, and a-pinene.